Drug-drug interactions for therapeutic biologics - Zhou, Honghui; Meibohm, Bernd (John Wiley & Sons, 2013)
Strategize, plan, and execute comprehensive drug-drug interaction assessments for therapeutic biologics Offering both theory and practical guidance, this book fully explores drug-drug interaction assessments for therapeutic biologics during the drug development process. It draws together and analyzes all the latest findings and practices in order to present our current understanding of the topic and point the way to new research. Case studies and examples, coupled with expert advice, enable readers to better understand the complex mechanisms of biologic drug-drug interactions.>